ETOP, the reference conference in Education and Training in Optics and Photonics. An overview of the 12th edition - Costa, Manuel F. M. (2014)
The Education and Training in Optics, ETOP, conferences are since 1988 one of the most important and relevant meetings in the field and a reference biennial conference that brings together the international community of optics and photonics educators, the academia and the industry, from all around the world to share experiences and information about learning and teaching optics and photonics at all levels. In this communication we will present the 12th ETOP’ edition that toke place rather successfully in Portugal in July 2013 with 214 participants from 38 countries and 140communications.